IMF Staff papers : Volume 21 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1974)
This paper presents main characteristics of a typical oil economy. Estimates of proven oil reserves in Saudi Arabia differ widely, ranging from estimates by ARAMCO and the other companies of about 100 billion barrels to figures exceeding 150 billion barrels. In 1969, two US firms commissioned by the Saudi Arabian Government completed studies of the country's oil reserves, estimating 126.4 billion barrels for the fields surveyed. Growth of oil production in Saudi Arabia has been determined largely by exogenous factors connected with the growth of world demand for oil and fluctuations in supplies from other producing areas. Industrial and agricultural development in Saudi Arabia has been constrained by the scarcity of natural resources, other than oil. Agricultural and fishery resources can be potentially significant, but only recently have they been systematically explored. Based on a clear comparative advantage in the supply of oil and natural gas, industrial development in Saudi Arabia is proceeding from oil production and refining to petrochemicals and to other energy-intensive industries.